Pemberdayaan Masyarakat melalui Pengembangan Olahan Ikan Asap Sagarurung di Kecamatan Talang Ubi Kabupaten Pali - Muhammad Raihan Febriansyah (Fakultas Dakwah IAIN Jember, 2023)
Community empowerment aims to empower individuals within a community to realize their full potential and skills. The community referred to is one where there is no one who is unproductive or unemployed. Unemployment is a state where members of the labor force do not have a job and are not actively seeking one at the moment. Unemployment can be addressed, one of which is through community empowerment by developing food processing, particularly those made from fish. If good operational and marketing practices are not followed by good fish processing development efforts, then there will be no high economic benefits or value. Qualitative research methods were applied in this study. The results of this study are: 1) The researcher concluded that the community empowerment process through the development of smoked sagarurung fish products in the Talang Ubi District of PALI Regency consists of several stages, namely community involvement, program planning, program implementation, and continuous evaluation. 2) Supporting factors for community empowerment are the facilities provided by the government and related agencies, while inhibiting factors include changes in mindset, the dominance of raw materials sourced from outside the region, and a lack of understanding of digital marketing. 3) The results of community empowerment are an increase in the life skills of smoked sagarurung fish business owners, fulfillment of their economic needs, and an increase in their understanding of high-quality smoked sagarurung fish processing.